ChemInform Abstract: Synthesis of Indolizine Derivatives by Pd‐Catalyzed Oxidative Carbonylation. Issue 5 (January 2016) - Xu, Tongyu; Alper, Howard
Abstract: Pd‐catalyzed three component reactions of propargylic pyridines, alcohols, and carbon monoxide afford a wide variety of highly functionalized indolizine derivatives.